HYPERURICEMIA AS AN EARLY MARKER OF KIDNEY FUNCTION DISORDERS IN YOUTH (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This study examines hyperuricemia as an early marker of kidney function impairment in youth. Elevated serum uric acid levels may reflect subclinical changes in glomerular filtration, tubular function, and renal microcirculation even in apparently healthy young individuals. The paper reviews the physiological role of uric acid, its impact on renal parameters, and the mechanisms by which hyperuricemia can contribute to kidney dysfunction. Early identification of elevated uric acid levels allows for timely preventive interventions, including lifestyle modifications, dietary adjustments, and increased physical activity. Monitoring uric acid alongside kidney function parameters provides a valuable tool for risk assessment, early diagnosis, and long-term preservation of renal health in the young population.